Inside the Black Box of Internet Adoption: The Role of Migration and Networking in Internet Penetration in West Africa. Issue 4 (19th April 2015) - Taylor, Linnet
Abstract : Research on the role of international networking and mobility in technology transfer to developing countries has focused on the firm level, looking at either spillovers from clusters of foreign firms or international trade. However this leaves micro‐level processes of adoption in more marginal areas a "black box"—a knowledge gap that is problematic for policymakers because technological inequalities between rich and poor within developing countries suggest that new technologies often fail to spread as hoped. This article offers empirical evidence on processes of Internet access provision and adoption at the micro‐level in Ghana, with particular attention to the importance of international mobility as a way for small‐scale entrepreneurs, so far a neglected resource in Internet penetration policy, to access technological resources and knowledge. Using a mixed methods approach combining fuzzy‐set Qualitative Comparative Analysis and social network analysis, this article argues that international mobility and networking are an important but neglected factor in technology access and adoption, contributing to Internet penetration into marginalized areas where usership was previously rare or nonexistent.